Maternal education and child mortality in Ecuador: cross-sectional analysis - Banderas, Valeria (2021)
The objective of this work is to evaluate the effect of maternal education on infant mortality in Ecuador. Data from the 2010 census and educational infrastructure records are used. To address endogeneity, on the one hand, reverse causality is considered for mothers between 23 and 34 years old. They are more likely to finish high school and avoid medical risks to their children. On the other hand, instruments are constructed to evaluate the omitted variables. They consider opening primary and secondary schools in the woman's birthplace when she was 17 years old. In addition, some mechanisms to reduce infant mortality are analyzed. However, they do not seem to be important for losing the first child, but they are important for surviving a child under the age of five. The gross effect of maternal education on infant mortality is negative. This influence is significant for infant and child mortality.